KAJIAN DEFOLIASI SORGUM PADA TUMPANGSARI DENGAN KACANG HIJAU*) - Donatus Kantur (Partner, 2008)
Study on Defoliation of Sorghum under Cropping Pattern by Mungbean.Â  The aim of the research was to find out the effect of defoliation of sorghum under cropping pattern toward the yield of sorghum, Mungbean and total relative result of the best sorghum and Mungbean in intercropping system has been carried out in Kebun Percobaan Fakultas Pertanian Universitas Gadjah Mada in Banguntapan, Bantul Regency from February up to June 2006. The research method used was split plot design with 2 factors and 3 repetitions. The main factor was defoliation of sorghum comprising of 2 levels: sorghum defoliation (D1) and without sorghum defoliation (D2). The sub factor of sub was cropping pattern, comprising of 5 levels: monoculture of Mungbean (H100). 75% sorghum: 25% Mungbean (S75 H25), 50% sorghum: 50% Mungbean (S50 H50), 25% sorghum: 75% Mungbean (S25 H75) and monoculture sorghum (S100). The results of the study showed that 1) the defoliation sorghum did not affect the yield of mungbean and sorghum, 2) cropping pattern of mungbean monoculture resulted bean/plant amount, seed/plant weight and seed weight/ha of mungbean as higher compared to other cropping pattern, 3) cropping pattern of 25% sorghum: 75% mungbean resulted seed weight/malai sorghum was higher compared to other planting patterns and the highest seed weight/ hectare was resulted in sorghum monoculture planting pattern, 4) the highest total relative yield was 1,303 given planting pattern at 50% sorghum: 50% mungbean and 5) the form of the relation between sorghum and mungbean in intercropping pattern and sorghum defoliation was complementary, while intercropping and without sorghum defoliation was supplementary.Keywords: defoliation, intercropping, result of mungbean and sorghum, total relative yield